Age-dependent effect of Alzheimer’s risk variant of CLU on EEG alpha rhythm in non-demented adults - Ponomareva, Natalya; Andreeva, Tatiana; Protasova, Maria; Shagam, Lev; Goltsov, Andrey; Malina, Daria; Fokin, Vitaly; Mitrofanov, Andrey; Rogaev, Evgeny (Frontiers in Aging Neuroscience, 2013)
Polymorphism in the genomic region harboring the CLU gene (rs11136000) has been associated with the risk for Alzheimer’s disease (AD). CLU C allele is assumed to confer risk for AD and the allele T may have a protective effect. We investigated the influence of the AD-associated CLU genotype on a common neurophysiological trait of brain activity (resting-state alpha-rhythm activity) in non-demented adults and elucidated whether this influence is modified over the course of aging. We examined quantitative EEG (qEEG) in cohort of non-demented individuals (age range 20-80) divided into young (age range 20-50) and old (age range 51-80) cohorts and stratified by CLU polymorphism. To rule out the effect of the ApoE genotype on EEG characteristics, only subjects without the ApoE epsilon4 allele were included in the study. The homozygous presence of the AD risk variant CLU CC in non-demented subjects was associated with an increase of alpha3 absolute power. Moreover, the influence of CLU genotype on alpha3 was found to be higher in the subjects older than 50 years of age. The study also showed age-dependent alterations of alpha topographic distribution that occur independently of the CLU genotype. The increase of upper alpha power has been associated with hippocampal atrophy in patients with mild cognitive impairment (Moretti et al., 2012a). In our study, the CLU CC- dependent increase in upper alpha rhythm, particularly enhanced in elderly non-demented individuals, may imply that the genotype is related to preclinical dysregulation of hippocampal neurophysiology in aging and that this factor may contribute to pathogenesis of AD.